2021
DOI: 10.3390/microorganisms9030598
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Different Sequencing and Assembly Approaches on the Detection of Plasmids and Localization of Antimicrobial Resistance Genes in Commensal Escherichia coli

Abstract: Antimicrobial resistance (AMR) is a major threat to public health worldwide. Currently, AMR typing changes from phenotypic testing to whole-genome sequence (WGS)-based detection of resistance determinants for a better understanding of the isolate diversity and elements involved in gene transmission (e.g., plasmids, bacteriophages, transposons). However, the use of WGS data in monitoring purposes requires suitable techniques, standardized parameters and approved guidelines for reliable AMR gene detection and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 73 publications
4
34
0
Order By: Relevance
“…Our comparison of the Illumina-and PacBio-generated genomes for the original stock 405D culture revealed no SNPs between these sequences, indicating comparable accuracy with both platforms. It has also been previously reported that small plasmid sequences may not be identified using the PacBio platform [52,53], and this was seen in our results, with sequences for two small plasmids (pARD3079 and p405tetH) found in all of the draft genomes, but not the PacBio sequence. It should be noted that the presence of the two plasmids will not affect the use of the strains as serovar controls, but has the potential to introduce variation into other types of studies, e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Our comparison of the Illumina-and PacBio-generated genomes for the original stock 405D culture revealed no SNPs between these sequences, indicating comparable accuracy with both platforms. It has also been previously reported that small plasmid sequences may not be identified using the PacBio platform [52,53], and this was seen in our results, with sequences for two small plasmids (pARD3079 and p405tetH) found in all of the draft genomes, but not the PacBio sequence. It should be noted that the presence of the two plasmids will not affect the use of the strains as serovar controls, but has the potential to introduce variation into other types of studies, e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Detection of qnr gene-carrying fragments was performed by Southern blotting and DNA-DNA hybridisation of S1-PFGE agarose gels. Hybridisation was conducted using digoxigenin-labelled (Roche Diagnostics, Mannheim-Penzberg, Germany) PCR probes of qnr genes and were prepared as previously described [ 23 ] ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Clinically associated fluoroquinolone resistance is mainly caused by chromosomal mutations in the quinolone resistance-determining regions (QRDRs) of gyrA and parC 22 , 23 . Furthermore, the cooccurrence of plasmid-mediated quinolone resistance (PMQR) genes and QRDR mutations can lead to high resistance (fluoro)quinolone phenotypes 24 . Recently, high percentages of ciprofloxacin resistance in ESBL-producing E. coli (50.5%) and K. pneumoniae (67.9%) from process and wastewater of poultry slaughterhouses have been reported 17 .…”
Section: Discussionmentioning
confidence: 99%